Carcinogenesis in Ulcerative Colitis: Is Surveillance Worthwhile? - ATR Axon (Canadian Journal of Gastroenterology)
Observations that dysplastic epithelium predicts neoplastic change in the coli tic bowel have led to the adoption of surveillance policies in ulcerative colitis patients, usually involving colonoscopy irrespective of symptomatology. Few satisfactory prospective studies of surveillance have been carried out. The present data suggest that patients should be screened at 10 years and investigated when symptomatic. Annual clinical review with five-yearly colonoscopic examination may be more reasonable, lead to better compliance, detect the occasional early cancer, and reduce the colonoscopic load.